THE ROLE OF WOMEN IN THE DAKWAH OF MUHAMMADIYAH - Tsalitsa Noor Kamila; Vivi Indri Asrini (Edusoshum : Journal of Islamic Education and Social Humanities, 2023)
The era of national awakening witnessed that women have a contribution, with the awareness to organize and coalition. This study aimed to investigate in detail the role of women in Muhammadiyah da'wah, focusing on the Aisyiyah organization.  This research uses a qualitative approach with literature study methods and content analysis. Data was collected from a variety of sources, including history books, Muhammadiyah da'wah literature, interviews with Muhammadiyah figures, as well as official organizational documents. Content analysis was used to unearth information about the concrete role of women in Muhammadiyah da'wah and the challenges they face. The results showed that Muhammadiyah women have a significant role in spreading Islamic teachings, especially through Aisyiyah organizations. Its position as a special autonomous organization, in contrast to other Muhammadiyah autonomous organizations, also has a fairly effective role to spread da'wah to the community in various aspects, (1) the field of religion, the Aisyiyah women's movement conducts da'wah through recitation, commemoration of Islamic holidays. Da'wah media carried out through magazines, radio to television. Also with the delivery of muballighat assigned to several places (2) social fields, with orphans and health facilities for the community.